SATISFACTION OF OUTPATIENTS IN WARD OF CONSULTING ROOM, TIEU CAN GENERAL HOSPITAL, IN TRA VINH PROVINCE IN 2020 (Vietnam Journal of Community Medicine, 2020)
Research on the satisfaction of 260 outpatient patients at Tieu Can general hospital. Methodology: Cross-sectional studies. Interview the subjects with the hospital quality assessment toolkit of the MOH. Results: The results show that, an accessibility satisfaction was 41.9%. Transparency of information and medical examination and treatment procedures reached 47.7%, facilities and equipments for patients reached 58.1%. Satisfaction, behavioral attitude, professional capacity of health workers reached the rate of 33.1%, satisfaction with the quality results of service delivery 37.3%. Conclusion: Patient satisfaction on outpatient care is relatively low.
Keywords: Satisfaction, outpatient, clinic.